(untitled) - White, Ron (London, 1997)
Process Writing is a resource book which develops writing proficiency through the recursive techniques of "process writing". The book comprises a collection of procedures and lesson formats divided into six main sections, enabling teachers to dipin and create their own writing programme according to the needs of their students.
Keywords: English language,English language; Compositions and exercises,Study and teaching,Foreign speakers,Study and teaching